Using the ISO 19761 COSMIC Measurement Standard to Reduce “Information Asymmetry” in Software Development Contracts and Enable Greater Competitiveness - Souto, Francisco Valdés; Abran, Alain (Scientific Research, 2013)
In most economic transactions involving software development projects, differences in the amount and quality of information possessed by economic agents (i.e. producers and customers) can lead to significant market inefficiencies. This paper describes the way the information derived from the functional size of software measured using the ISO 19761 COSMIC measurement standard that can help reduce information asymmetry in software development transactions, and lead to increased competitiveness in the software industry.
Keywords: Software Projects; COSMIC; Information Asymmetry; ISO 19761; Software Industry Competitiveness; Software Characterization; Software Facts